EVALUASI PENYELENGGARAAN LATIHAN UJIAN NASIONAL BAHASA INGGRIS SMA SWASTA EX-RSBI - Noor, Widya Noviana; Aman, Aman (Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
Penelitian ini bertujuan (1) memperoleh informasi input (antecedents) tentang penyelenggaraan latihan UN, (2) mengetahui proses (transactions) penyelenggaraan latihan UN, dan (3) mengetahui hasil (outcomes) penyelenggaraan latihan UN Mata Pelajaran Bahasa Inggris. Model evaluasi yang digunakan model Stake's. Subjek yang digunakan (1) Dinas Pendidikan Kota Yogyakarta; (2) SMA Swasta ex-RSBI kelas XII di kota Yogyakarta. Teknik pengambilan sampel secara simple random sampling. Sumber data adalah Dinas Pendidikan Kota Yogyakarta, kepala sekolah, dan siswa. Hasil penelitian adalah (1) input (antecedents) penyelenggaraan latihan UN sudah baik dilihat dari dimensi persiapan penyelenggaraannya; (2) proses (transaction) penyelenggaraan latihan UN Mata Pelajaran Bahasa Inggris baik; (3) pada hasil (outcomes) menunjukkan analisis kualitas butir soal baik, terlihat dari tingkat kesukaran butir sedang (50%), daya beda baik (70%), distraktor berfungsi dengan baik (58%) dan reliabilitas butir termasuk tinggi (0,851). Latihan UN memberikan manfaat cukup baik dan tidak terdapat hambatan dalam penyelenggaraan latihan UN Mata Pelajaran Bahasa Inggris.Kata kunci: tryout, model Stake's (antecedents, transactions dan outcomes), Bahasa Inggris. AN EVALUATION OF THE IMPLEMENTATION OF ENGLISH NATIONAL EXAMINATION EXERCISE AT EX-RSBI PRIVATE SMAAbstractThis study aims to (1) obtain the information of the input (antecedents) of English tryout (2) document the process (transactions) of the implementation, and (3) determine the results (outcomes) of the implementation of English tryout. Evaluation model that is used is the Stake's model. The subjects in this research are (1) the Education Office of Yogyakarta; (2) the students of Ex RSBI Private SMA in Yogyakarta. The technique of selecting sampling was by stratified random sampling. The sources of the data at the Regency level is the Education Office of Yogyakarta, principals, and students. The results are (1) the input of the implementation is good if it is viewed from the dimensions of the preparation that include the orientation of question writing, committee, schedule and supervision; (2) process is good if it is viewed from the dimensions of the implementation that included security matter, objectivity of the implementation, and students' perceptions; (3) results show that question items are good. It can be seen from the difficulty of each question that is in medium (50%), good different power (70%), the distractor is functioning properly (58%) and reliability in the high category (0.851). English tryout gives good benefits and there are no obstacles in the implementation of English tryout.Keywords: tryout, Stake's model (antecedents, transactions and outcomes), English